Inactivation of Myosin Binding Protein C Homolog in Zebrafish as a Model for Human Cardiac Hypertrophy and Diastolic Dysfunction. Issue 5 (18th September 2013) - Chen, Yau‐Hung; Pai, Chiung‐Wen; Huang, Shu‐Wei; Chang, Sheng‐Nan; Lin, Lian‐Yu; Chiang, Fu‐Tien; Lin, Jiunn‐Lee; Hwang, Juey‐Jen; Tsai, Chia‐Ti
Abstract : Background: Sudden cardiac death due to malignant ventricular arrhythmia is a devastating manifestation of cardiac hypertrophy. Sarcomere protein myosin binding protein C is functionally related to cardiac diastolic function and hypertrophy. Zebrafish is a better model to study human electrophysiology and arrhythmia than rodents because of the electrophysiological characteristics similar to those of humans. Methods and Results: We established a zebrafish model of cardiac hypertrophy and diastolic dysfunction by genetic knockdown of myosin binding protein C gene ( mybpc3 ) and investigated the electrophysiological phenotypes in this model. We found expression of zebrafish mybpc3 restrictively in the heart and slow muscle, and mybpc3 gene was evolutionally conservative with sequence homology between zebrafish and human mybpc3 genes. Zebrafish with genetic knockdown of mybpc3 by morpholino showed ventricular hypertrophy with increased myocardial wall thickness and diastolic heart failure, manifesting as decreased ventricular diastolic relaxation velocity, pericardial effusion, and dilatation of the atrium. In terms of electrophysiological phenotypes, mybpc3 knockdown fish had a longer ventricular action potential duration and slower ventricular diastolic calcium reuptake, both of which are typical electrophysiological features in human cardiac hypertrophy and heart failure. Impaired calcium reuptake resulted in increased susceptibility to calcium transient alternans and action potential duration alternans, which have been proved to be central to the genesis of malignant ventricular fibrillation and a sensitive marker of sudden cardiac death. Conclusions: mybpc3 knockdown in zebrafish recapitulated the morphological, mechanical, and electrophysiological phenotypes of human cardiac hypertrophy and diastolic heart failure. Our study also first demonstrated arrhythmogenic cardiac alternans in cardiac hypertrophy.